AMTHA : an algorithm for automatically mapping tasks to processors in heterogeneous multiprocessor architectures - De Giusti, Laura Cristina
An automatic task-to-processor mapping algorithm is analyzed in parallel systems that run over loosely coupled distributed architectures. The MPAHA (Model on Parallel Algorithms on Heterogeneous Architectures) model that allows predicting parallel application performance running over heterogeneous architectures is presented. In particular, the heterogeneity of both processors communications is taken into consideration. the results obtained with the MPAHA model, the AMTHA (Automatic Mapping Task on Heterogeneous Architectures) algorithm for task-toprocessors assignment is presented its implementation is analyzed. Experimental results compare execution time obtained with AMTHA mapping scheme with those obtained using the known mapping algorithm HEFT (Heterogeneous – Earliest Finish – Time), using asimple heterogeneous multicluster architecture.Finally actual lines of research are presented,focusing extensions to multicore processors Gridenvironments.